KEBIASAAN KONSUMSI MIE INSTAN DAN AKTIVITAS FISIK DENGAN STATUS GIZI PADA REMAJA SMA TAMAN HARAPAN 1 KOTA BEKASI - Fika Rachmawati (2023)
Based on Riskesdas data for 2018, there were 16.0% and 13.5% of adolescents who were overweight or obese, respectively. The existence of this technological development has changed the eating patterns of teenagers to become fond of consuming junk food such as instant noodles, which will have an impact on their nutritional status. Technological developments have also changed the movement patterns of adolescents to become more inactive in carrying out physical activities, which will result in a lower nutritional status. This study aims to analyze the relationship between instant noodle consumption habits and physical activity on the nutritional status of adolescents at SMA Taman Harapan 1 Bekasi. This research method is analytic-observational with a cross-sectional study design that has a sample size of 84 respondents, and the sample is taken using a simple random sampling method. The results of the bivariate test analysis using chi-square showed that there was a relationship between instant noodle consumption habits and the nutritional status of SMA Taman Harapan 1 Bekasi students (p = 0.003). However, it did not show a relationship between physical activity and the nutritional status of SMA Taman Harapan 1 Bekasi students (p = 0.217). Daoat concluded that there was a relationship between consumption habits of instant noodles and nutritional status, but there was no relationship between physical activity and nutritional status.